Nakaparsuaan, Kadagaan, and Panaglunit ti Daga: Climate Justice and Environmental Ethics in Ilokano Life - Agcaoili, Aurelio S. (Archīum Ateneo, 2024)
The work offers an interpretation of the world as understood and being lived until today by Ilokanos. Such a reading involves the plumbing into linguistic and cultural data as proofs of an inchoate philosophy that has been preserved in the minds of the Ilokano people and which continues to guide their conduct. The world, understood as the physical environment, peoples, and communities, is linked back to the problem of social justice and stewardship of living and nonliving things, to the issue of who calls the shots in the unethical exploitation of these resources, and to the lessons that can be learned from how the Ilokanos have understood their place in the cosmos where ethical co-existence is required and where care of the environment is a must.